Association between DCP levels and kidney stone prevalence in US female adults based on NHANES data - Heqian Liu; Jiawei Wang; Lingsong Tao; Yunwu Hao (Scientific Reports, 2024)
Abstract Our study aimed to evaluate the correlation between levels of 2,4-DCP(2,4-Dichlorophenol) and 2,5-DCP(2,5-Dichlorophenol) and the prevalence of kidney stones in US female adults. Participants were chosen from the National Health and Nutrition Examination Survey database, spanning the years 2007–2016. Dose–response curves were analyzed using logistic regression, subgroup analyses, and other statistical methods to evaluate the relationship between 2,4-DCP and 2,5-DCP levels and the prevalence of kidney stones. The final study included 3220 participants aged over 20 years, with 252 females reporting a history of kidney stones. After accounting for all interfering variables, we found that every 0.1 ug/ml increase in 2.4-DCP correlated with a 1% rise in kidney stone prevalence (OR = 1.01, 95% CI 1.00, 1.01), whereas the same increase in 2.5-DCP was linked to a 27% growth in prevalence (OR = 1.27, 95% CI 1.01, 1.61). Sensitivity analysis was performed by triangulating 2,4-DCP and 2,5-DCP levels. The dose–response curves demonstrated a linear positive relationship between 2,4-DCP and 2,5-DCP levels and the risk of stone development. Our findings indicate a positive correlation between 2,4-DCP and 2,5-DCP levels and the prevalence of kidney stones in US female adults. This association is of clinical significance; however, a direct causal relationship cannot be definitively established.